Effects of Phase-Locking Deficits on Speech Recognition in Older Adults With Presbycusis - Hao, Wenyang; Wang, Qian; Li, Liang; Qiao, Yufei; Gao, Zhiqiang; Ni, Daofeng; Shang, Yingying (Frontiers in Aging Neuroscience, 2018)
Objective: People with presbycusis often report difficulties in speech recognition, especially under noisy listening conditions. Investigating the presbycusis-related changes in central representations of envelope signals and temporal fine structure (TFS) signals of speech sounds is critical for understanding the mechanism underlying the presbycusis-related deficit in speech recognition. Frequency-following responses (FFRs) to speech stimulation can be used to examine the subcortical encoding of both envelope and TFS speech signals. This study compared FFRs to speech signals between listeners with presbycusis and those with clinically normal hearing under either quiet or noise-masking conditions. Methods: FFRs to a 170-ms speech syllable /da/ were recorded under either a quiet or noise-masking (with a signal-to-noise ratio of 8 dB) condition in 14 older adults with presbycusis (PC) and 13 age-matched adults with normal hearing (NH). The envelope (FFRENV) and TFS (FFRTFS) components of FFRs were analyzed separately by adding and subtracting the alternative polarity responses, respectively. Speech recognition in noise was evaluated in each participant. Results: In the quiet condition, compared with the NH group, the PC group exhibited smaller F0 and H3 amplitudes and decreased stimulus-response (S-R) correlation for FFRENV but not for FFRTFS. Both the H2 and H3 amplitudes and the S-R correlation of FFRENV significantly decreased in the noise condition compared with the quiet condition in the NH group but not in the PC group. Moreover, the degree of hearing loss was correlated with noise-induced changes in FFRTFS morphology. Furthermore, the speech-in-noise (SIN) threshold was negatively correlated with the noise-induced change in H2 (for FFRENV) and the S-R correlation for FFRENV in the quiet condition. Conclusion: Audibility affects the subcortical encoding of both envelope and TFS in presbycusis patients. The impaired ability to adjust the balance between the envelope and TFS in the noise condition may be part of the mechanism underlying presbycusis-related deficits in speech recognition in noise. FFRs can predict SIN perception performance.